PERAN PEMERINTAH DAERAH DALAM MENGAWASI PENGELOLAAN JASA PENITIPAN ANAK DI KOTA DEPOK: The Role of Local Government in Supervising the Management of Childcare Service in Depok City - Syafira Zahra Nurasila; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
This research discusses the role of local government in supervising child care services in Depok City. In the modern era, the complexity of life's problems requires both parents to work, which often creates challenges in childcare. Daycare centers (TPA) are a solution, but many TPAs in Depok are not officially registered, only 12 are officially registered, so there are still many that have the potential to endanger children. This problem of the study, namely whether the supervision of child care services is in accordance with the provisions of a child-friendly city in Depok City. This study uses normative juridical research methods, with secondary data from relevant laws and regulations. The results and conclusion of the discussion show that the supervision carried out by the government is still weak, with many TPAs not meeting quality standards. Improved regulations and supervision are needed to protect children's rights and increase public trust in the government.